L-arginine metabolism in early-onset and late-onset pre-eclamptic pregnancies. (August 2013) - Tamás, Péter; Bódis, József; Sulyok, Endre; Kovács, Gábor L.; Hantosi, Eszter; Molnár, Gábor; Martens-Lobenhoffer, Jens; Bode-Böger, Stefanie M.
Abstract Objective. The present case-control study was undertaken to investigate l-arginine metabolism in pregnant women with early-onset and late-onset pre-eclampsia. Attempts were made to differentiate these two distinct diseases entities by using measured and derived parameters of l-arginine metabolism. Study design. Thirty-six patients with early-onset, 17 patients with late-onset pre-eclampsia and 15 healthy pregnant women at term were studied. Patients were categorized according to the weeks of gestation (< 34 vs. ≥ 34) at the appearance of clinical symptoms (hypertension + proteinuria). Venous samples were taken at gestational age of 29.8 ± 2.5, 36.1 ± 2.2 and 39.2 ± 1.2 weeks, respectively. L-arginine, asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), monomethylarginine (MMA) and l-ornithine were measured by LC-MS/MS method. L-arginine/ADMA, l-ornithine/l-arginine, ADMA/SDMA ratios and the arginine methylation index (arg-MI) were calculated. Results. Plasma levels of ADMA and MMA were significantly higher (p < 0.002) in pre-eclamptic patients than in healthy women. No significant differences could be detected between patients with early-onset and late-onset pre-eclampsia in either parameter studied. L-ornithine correlated positively with ADMA (r = 0.526, p < 0.001) and MMA (r = 0.533, p < 0.001) in the whole study population, and inversely with l-arginine (r = − 0.277, p < 0.044) in the pre-eclamptic group. When compared with maternal plasma in venous cord blood l-arginine was markedly reduced (p < 0.05) and there was a significant elevation in ADMA, SDMA, MMA and l-ornithine (p < 0.001, for each) without discernible differences between the study groups. Conclusions. Parameters of l-arginine metabolism do not discriminate the early-onset from late-onset pre-eclampsia. Our study provided indirect evidences for the redirection of l-arginine-NOS to the l-arginine-arginase pathway.